Reconstructivism: On Honneth's Hegelianism. (October 2014) - Pippin, Robert
In this paper I express enthusiastic solidarity with Axel Honneth's inheritance and transformation of several core Hegelian ideas, and express one major disagreement. The disagreement is not so much with anything he says, as it is with what he doesn't say. It concerns his rejection of Hegel's theoretical philosophy, and so his attempt to reconstruct Hegel's practical philosophy without reliance on that theoretical philosophy. This attitude towards Hegel's Science of Logic – that it involves a "mystification" of essentially practical notions - has been typical of the Critical Theory tradition since Marx, and is disputed here. It also helps to raise the large issue of the proper understanding of the relation between theoretical and practical philosophy. The implications of ignoring the Hegelian understanding of this dependence of the latter on the former are further developed.